Airside Heat Transfer and Friction Characteristics of a 0.8 mm Diameter Bare Tube Heat Exchanger. Issue 19 (12th November 2020) - Huang, Zhiwei; Ling, Jiazhen; Hwang, Yunho; Aute, Vikrant; Radermacher, Reinhard
Abstract: An experimental study was conducted to investigate the airside thermal and hydraulic performance of a compact bare tube heat exchanger, which consists of 484 bare tubes with an outer diameter of 0.8 mm. Its performance is compared with a louvered-fin and flat-tube heat exchanger with the similar frontal surface, under the identical test condition matrix. The effects of air flow rate and water flow rate on total heat transfer capacity and pressure drop are discussed. From the experimental results, it was found that compared with the baseline heat exchanger, this bare tube heat exchanger can achieve the same heat capacity with 72% less envelop volume and 70% less material volume. Heat transfer and friction performance are evaluated using Chilton-Colburn j and f factor. The j / f value of bare tube heat exchanger is 50% higher than that of the baseline heat exchanger. Chilton-Colburn j and f power law correlations were developed for Reynolds number range of 190–420. Discrepancies between experimental data and new correlation are both within ±5%.